Analysis of Students' Perceptions of Google Translate as a Translator Media - Indra Purnawan Panjaitan; Farida Maricar (Humanitatis : Journal of Language and Literature, 2022)
Google Translate is a digital language translation service launched by a well-known digital company, Google. Its multilingual service has been widely used by internet users. Users use it to translate foreign languages or opposite. The research method used to examine student perceptions of the Google Translate as a translator medium is a qualitative method. Qualitative research approach is research to understand the phenomenon about what is assessed based on research subjects such as behavior, perception, motivation, action. Almost final semester students of Khairun University, English Literature Program use the Google Translate application as a medium for translating their final assignments on the grounds that Google Translate is easy to use. Although Google Translate has shortcomings in the selection of diction that must be corrected one by one word, but students' perceptions of this application remain positive, they assume that the translation results will remain accurate if they can match the context being discussed. They are very helpful with the application.